2014
DOI: 10.5901/mjss.2014.v5n15p76
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Monetary Policy on Economic Growth: A Case Study of South Africa

Abstract: This paper explores the role played by monetary policy in promoting economic growth in the South African economy over the period [2000][2001][2002][2003][2004][2005][2006][2007][2008][2009][2010]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 11 publications
5
26
0
2
Order By: Relevance
“…When money supply increases by a unit, gross domestic product increases by 0.491614 units. This result is supported by the study of Precious and Palesa (2014) who showed that money supply significantly and positively influences economic growth in the long run in South Africa. Also, we found out that interest rate has a significant negative relationship with gross domestic product.…”
Section: Vector Error Correction Model (Vecm)supporting
confidence: 55%
See 1 more Smart Citation
“…When money supply increases by a unit, gross domestic product increases by 0.491614 units. This result is supported by the study of Precious and Palesa (2014) who showed that money supply significantly and positively influences economic growth in the long run in South Africa. Also, we found out that interest rate has a significant negative relationship with gross domestic product.…”
Section: Vector Error Correction Model (Vecm)supporting
confidence: 55%
“…The Vector Error Correction Models (VECM) is a confined VAR intended for use with non-stationary series that are recognized to be co-integrated with an Error Correction Term (ECT) built into the model (Precious and Palesa 2014). The Error Correction Term calculates every deviation from the long-run equilibrium.…”
Section: Vector Error Correction Model (Vecm)mentioning
confidence: 99%
“…Results indicate that monetary policy indicators exert a negative impact on economic growth and by extension to the financial stability and development, respectively. Likewise, Precious and Palesa (2014) examine the essential role played by the monetary policy in promoting economic growth in the South African economy over the sample period of 2000 to 2010 [36]. Using the Johansen cointegration and the error correction mechanism to evaluate the long-run and short-run relationship, findings indicate the existence of a long-run relationship among the concerned variables.…”
Section: Negative Impact Of Monetary Policymentioning
confidence: 99%
“…Many empirical studies, such as Sims [16], Grilli and Roubini [6], Kim and Roubini [8], Neril and Novili [15], Li and Liang [10], Mirkov [13], Precious and Palesa [15], Barakchian [2], Bowman, et al [3], Lee and Zhu [9] have investigated the international transmission mechanism by using VAR models of developed and developing economies. Kim [7], for example, suggested that U.S. monetary policy shocks on the output of the developed countries had a positive effect.…”
Section: Introductionmentioning
confidence: 99%